Study Usage of Computational Fluid Dynamics (CFD) For Indoor Simulation - Jamaludin, Nurul Filzati; Mohamed Yusop, Fatimah; Saji, Nurdalila (Progress in Engineering Application and Technology, 2021)
Computational fluid dynamic (CFD) is an important tool that capable of solving fluid flow problems and estimating physical fluid flow and heat transfer. By using CFD, air flow can be simulated to accurately design spaces that provide the required flow and velocity. The wrong choice of a numerical method and a gridding technique in the solution of CFD problems it will give effect to get the accurate results. Thus, the aim of this study to investigate the application of CFD for indoor simulation and to identify the suitable turbulence model for indoor simulation by the lower percentage difference. The studies used information from the previous researches that used CFD simulation. The result shows the most turbulence model that be used is realizable k-ɛ with the percentage difference less than 10%. So that, realizable k-ɛ is the suitable turbulence model for indoor simulation with lowest percentage difference, occupy less computational resources and minimize computing time. Realizable k-ɛ model is recommended and the solution accuracy is higher than the others. In addition, Ansys Fluent is the most widely used code in indoor simulation because it is more user-friendly due to its user-defined functionality.